Is Gratitude linked to Life Satisfaction in Early Adulthood? - Monica Rusdiana Santoso; Marcella Mariska Aryono (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Early adulthood was prone to psychological problems such as stress, anxiety, unhappiness, depression caused by dissatisfaction in life. This dissatisfaction is because early adulthood requires one to be independently responsible for one’s life such as work, education, relationships, and finance. One of the factors that leads individuals to life satisfaction is gratitude, where gratitude forms a positive understanding, and it has been shown to prevent depression and stress. The purpose of this study is to test whether there is a relationship between early adult life satisfaction and coexistence in Madiun City. The number of samples in this study was 200 early adults, with quota sampling techniques. Data collection uses the scale of coexistence and the scale of life satisfaction that researchers have compiled. Based on the hypothesis test results of 0.000 (p ± 0.05) with a coefficient correlation value of 0.745 the hypothesis is accepted that there is a significant relationship between life satisfaction variables and early adulthood in Madiun City. The higher the size, the higher the life satisfaction, the higher the early adulthood in Madiun City, and the lower the life satisfaction, the lower the early adulthood in Madiun City.Pada masa dewasa awal rentan muncul permasalahan-permasalahan psikologis seperti stres, cemas, tidak bahagia, depresi yang disebabkan adanya ketidakpuasan dalam hidupnya. Ketidakpuasan ini dikarenakan dewasa awal dituntut dapat bertanggungjawab secara mandiri terhadap kehidupannya seperti pekerjaan, pendidikan, hubungan relasi dan finansialnya. Salah satu faktor yang membuat individu mendapatkan kepuasan hidup adalah rasa syukur, dimana rasa syukur mampu menciptakan pemahaman yang positif sehingga dapat mencegah depresi dan stres. Tujuan dari penelitian ini adalah untuk mengetahui apakah terdapat hubungan antara kepuasan hidup dan kebersyukuran pada masa dewasa awal di Kota Madiun. Jumlah sampel dalam penelitian ini terdapat 200 orang dewasa awal, dengan teknik quota sampling. Pengumpulan data menggunakan skala kebersyukuran dan skala kepuasan hidup yang disusun peneliti. Berdasarkan dari hasil analisis uji hipotesis yaitu sig 0,000 (p < 0,05) dengan nilai korelasi koefisien sebesar 0,745 maka hipotesis diterima yaitu terdapat hubungan yang signifikan antara variabel kepuasan hidup dengan kebersyukuran pada dewasa awal di Kota Madiun. Semakin tinggi kebersyukuran maka kepuasan hidup juga semakin tinggi pada dewasa awal yang ada di Kota Madiun, dan juga sebaliknya semakin rendah kebersyukuran maka kepuasan hidup juga semakin rendah pada dewasa awal yang ada di Kota Madiun.